Development of Effective Antileishmanial Herbal Drug from Withania Somnifera and Tinospora Cordifolia Extracts - Tiwari, Ritesh K.; Kumar, Ashish; Singh, Veer; Rai, Sachchida N.; Singh, Santosh K.; Ahmed, Ghufran; Vamanu, Emanuel; Singh, Meenakshi (Current Traditional Medicine, 2025)
BackgroundVisceral leishmaniasis is a vector-borne immune-related disease that manifests mainly by lowering of immune protective T-helper-1 cells and onset of disease-promoting T-helper-2 cells therefore the treatment of visceral leishmaniasis depends on boosting the immune status of the host.MethodsIn this study, two traditional medicinal plants Withania somnifera and Tinospora cordifolia were selected, and their whole plant extracts were used for treating visceral leishmaniasis-infected BALB/c mice. Observing the case of immune suppression and balance of Th-1/Th-2 dichotomy during visceral leishmaniasis in mind, the efficacy of these combined herbal drugs against visceral leishmaniasis infected mice was evaluated by monitoring the restoration of T-helper-1 type protective immune response.ResultsTo evaluate the effectiveness of these drugs against visceral leishmaniasis, reactive nitrogen species and reactive oxygen species were measured. Biochemical parameters were also performed from blood serum samples during this study, and normalized results were obtained in visceral leishmaniasis-infected mice treated with Withania somnifera and Tinospora cordifolia subgroup. The Amphotericin B treated subgroup was considered as standard positive control during the experiment.ConclusionA combination of herbal drugs resulted in a successful clearance of Leishmania parasite as well as increased immune protective T-helper-1 cells, suggesting these drugs as efficient antileishmanial agents.
Keywords: CL